Synthesis and Characterization of Some Mixed Ligand Complexes of Cu(II) with 2,2´ -Bipyridylamine and Phenols - N. PATEL, JAYSHREE; SHARMA, SANGITA; VORA, J.J.; JOSHI, J.D. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of Cu(lI) with 2.2'-bipyridylamine and phenols, viz., catechol, pyrogallol, 2,3-dihydroxynaphthalene or protocatechuic acid have been synthesised and characterised by modem methods like elemental analysis, infrared spectra, thermogravimetric analysis, magnetic moment, electronic spectra and conductivity measurements. All complexes are found to be coloured.